2009
DOI: 10.5397/cise.2009.12.1.021
|View full text |Cite
|
Sign up to set email alerts
|

Dose-related Effect of Extracorporeal Shock Wave Therapy for Lateral Epicondylitis - Prospective Randomized Double Blind Comparative Study -

Abstract: Purpose: The aim of this study was to examine the dose-related effect of extracorporeal shock wave therapy (ESWT) for lateral epicondylitis. Materials and methods: Thirty patients with refractory lateral epicondylitis despite conservative treatment for 6 months were enrolled in this study. The patients were divided randomly into a low-and highenergy group. All patients were treated 3 times with ESWT with an interval of 1 week in a double blinded manner. The mean energy level in the low-and high-energy group wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Looking into existing research supporting these results, a number of studies reported that the effects of extracorporeal shock wave therapy lasted up to 6 months along with excellent short-term effects 10,20,21. The effects of the therapy lasted until 8 weeks in this study.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Looking into existing research supporting these results, a number of studies reported that the effects of extracorporeal shock wave therapy lasted up to 6 months along with excellent short-term effects 10,20,21. The effects of the therapy lasted until 8 weeks in this study.…”
Section: Discussionsupporting
confidence: 63%
“…Looking into existing research supporting these results, a number of studies reported that the effects of extracorporeal shock wave therapy lasted up to 6 months along with excellent short-term effects. 10 , 20 , 21 The effects of the therapy lasted until 8 weeks in this study. In contrast, Speed et al 27 reported that extracorporeal shock wave therapy was not effective while patients with lateral epicondylitis were treated.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We used low energy shock wave in this study according to the definition of energy dose established by Speed [7] in 2004; here, 0.12 mJ/mm 2 is a cut of value and above doses was defined as high energy shock wave and below doses was as low energy shock wave. Rompe et al [18] and Oh et al [19] reported that responses of tendon to shockwaves are dependent on energy dose and high energy shock wave therapy is more effective in treatment. However local anesthesia might be required when a high energy delivered because of severe pain and also higher energy doses above 0.60 mJ/mm 2 could cause necrosis of tendon [18].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, applying extracorporeal shock wave treatment of low energy also had an effect on the improvement of muscle tone 12,14) , but the findings of the present study suggest that the effect of the treatment continued longer after the intervention in the high energy group than in the low energy group. Although the appropriate energy amount for reduction of muscle tone by extracorporeal shock wave treatment has not been clearly defined, 25,26) there was a study that found that high energy was more effective for treatment in the clinical application for musculoskeletal disorders. Most studies used intervention with a low energy in pediatric patients in consideration of adverse reactions such as psychological anxiety, redness, and pain.…”
Section: ⅳ Discussionmentioning
confidence: 99%